N-acetyltransferase 2 (NAT2) gene polymorphisms in Parkinson's disease - Borlak Juergen; Reamon-Buettner Stella Marie (BMC, 2006)
Abstract Background Parkinson's disease (PD) is a movement disorder caused by the degeneration of dopaminergic neurons in the substantia nigra of the midbrain. The molecular basis of this neural death is unknown, but genetic predisposition and environmental factors may cause the disease. Sequence variations in N-acetyltransferase 2 (NAT2) gene leading to slow acetylation process have been associated with PD, but results are contradictory. Methods We analyzed three NAT2 genetic variations, c.481C>T, c.590G>A (p.R197Q) and c.857G>A (p.G286E), which are known to result in a slow acetylator phenotype. Using validated PCR-RFLP assays, we genotyped 243 healthy unrelated Caucasian control subjects and 124 PD patients for these genetic variations. Further, we have undertaken a systematic review of NAT2 studies on PD and we incorporated our results in a meta-analysis consisting of 10 studies, 1,206 PD patients and 1,619 control subjects. Results Overall, we did not find significant differences in polymorphic acetylation genotypes in PD and control subjects. In the meta-analysis of slow acetylators from 10 studies and representing 604/1206 PD vs. 732/1619 control subjects, a marginally significant odds ratio (OR) of 1.32 (95% CI 1.12-1.54, p < 0.05) was obtained. Re-analysis of the data to exclude the only two studies showing positive association of slow acetylators to PD, resulted in a non-significant OR (1.07, 95% CI 0.9-1.28). Furthermore, meta-analysis of studies for c.590G>A, where both allele and genotype frequencies in PD vs. control subjects were analyzed, did not give significant summary odds ratios as well. Conclusion We found little evidence for differences in polymorphic acetylation genotypes in PD and control subjects. Results of the meta-analyses did not also provide conclusive evidence for an overall association of NAT2 slow acetylator genotypes to PD.